Comparison of The Effectiveness of Consuming Watermelon and Ambon Bananas on The Blood Pressure of Elderly People with Hypertension - Gemini, Savitri; Alba, Afif D.; Dharma, Fasida (Future Science, 2024)
Hypertension is a disease factor that affects around 1.3 billion adults worldwide, significantly increasing the risk of heart, brain, and kidney disease, is the main cause of death globally, claiming around 10.8 million lives. Treatment of hypertension can be pharmacological, by taking antihypertensive drugs and Non-pharmacological therapy, namely watermelon and Ambon banana therapy. This study aimed to see the difference in the effectiveness of consuming Ambon bananas and watermelon in reducing blood pressure in elderly people with hypertension. This type of research was quasi-experimental with a pre-post test design with the control group, of 15 elderly people treated with Ambon bananas and 15 elderly people treated with watermelon. Statistical tests use the independent t-test. The results of this study were obtained using an independent t-test for blood pressure, and systolic pressure, the t value was 2.219 > t table 2.048 with a p-value of 0.035 (intervention group), and the same t value was obtained, namely 2.219 > t table 2.048 with a p-value of 0.036 < ? 0.05 (control group). Meanwhile, for diastolic blood pressure, the t value was 2.435 > t table 2.048 with a p-value of 0.022 (intervention group) and the same t value was 2.435 > t table 2.048 with a p-value of 0.023 < ? 0.05 (control group).so it can be concluded that H0 is accepted, meaning there is a statistically significant difference in effectiveness consumption of Ambon bananas and watermelon reducing systolic and diastolic blood pressure in elderly people with hypertension in the work area work at the Jemaja Timur Anambas Community Health Center. Suggestions for further research: this research can provide information for further research related to the factors that cause hypertension.